2010
DOI: 10.1163/016942409x12538865056033
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Surface DBD Plasma Treatment on the Adhesion of Coatings to High-Tech Textiles

Abstract: The surface of high-performance poly(ethylene terephthalate) (PET) fibers is difficult to wet and impossible to chemically bond to different matrices. Sizing applied on the fiber surface usually improves fiber wetting, but prevents good adhesion between a matrix and the fiber surface.The present study demonstrates that the plasma treatment performed by Surface dielectric barrier discharge (Surface DBD) can lead to improved adhesion between sized PET fabric and polyurethane (PU) or poly(vinyl chloride) (PVC) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Plasma technology is broadly used to improve surface wettability and/or hydrophilicity of numerous textile materials (Demir et al, 2011;Ren et al, 2008). The increase in hydrophilicity of numerous fibrous materials such as polyamide, polyester, polyethylene, polypropylene, silk, aramid, carbon fibers, wool, and cellulose has been Sarmadi et al (1996) demonstrated (Riccardi et al, 2005;Masaeli et al, 2007;Li et al, 2009;Huang et al, 2013;Bessada et al, 2011;Simor et al, 2010;Wang and Qiu, 2007;Vander Wielen et al, 2006). Plasma treatments in air or using different carrier gases are able to introduce hydrophilic functional groups such as eCOOH, eOH, and eNH 2 on the fabric surface.…”
Section: Improving Textiles Hydrophilicity and Hydrophobicity By Plasmamentioning
confidence: 99%
“…Plasma technology is broadly used to improve surface wettability and/or hydrophilicity of numerous textile materials (Demir et al, 2011;Ren et al, 2008). The increase in hydrophilicity of numerous fibrous materials such as polyamide, polyester, polyethylene, polypropylene, silk, aramid, carbon fibers, wool, and cellulose has been Sarmadi et al (1996) demonstrated (Riccardi et al, 2005;Masaeli et al, 2007;Li et al, 2009;Huang et al, 2013;Bessada et al, 2011;Simor et al, 2010;Wang and Qiu, 2007;Vander Wielen et al, 2006). Plasma treatments in air or using different carrier gases are able to introduce hydrophilic functional groups such as eCOOH, eOH, and eNH 2 on the fabric surface.…”
Section: Improving Textiles Hydrophilicity and Hydrophobicity By Plasmamentioning
confidence: 99%
“…Although wettability of surfaces has been studied for centuries, new applications have emerged in recent decades with respect to the boundary between physics and biology. It influences many surface‐related processes, such as cell‐culture growth, coating adhesion, and so forth . The preparation of surfaces with controlled wetting, especially on polymer substrates, is still a hot topic .…”
Section: Introductionmentioning
confidence: 99%
“…It influences many surface-related processes, such as cell-culture growth, coating adhesion, and so forth. [1,2] The preparation of surfaces with controlled wetting, especially on polymer substrates, is still a hot topic. [3] Often tailor-made, polymers can be prepared by a variety of chemical (wet chemistry, sol-gel technique, and vapor depositions) and physical (plasma polymerization in either atmospheric or lower pressures) methods.…”
Section: Introductionmentioning
confidence: 99%
“…Surface dielectric barrier discharge (DBD) can generate uniform plasma layers with large areas at atmospheric pressure, so it is attractive for many industrial applications, such as ozone synthesis [1,2], surface treatment [3,4], thin-film deposition [5,6] and aerodynamic flow control [7][8][9]. Generally, surface DBD is produced in a thin layer along a dielectric surface at room temperature and atmospheric air.…”
Section: Introductionmentioning
confidence: 99%